VD_FINDINFO AI 199/14 - 231/2014 vom 16. September 2014 - VD Tribunal cantonal (2014)
COMPÉTENCE RATIONE LOCI, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, RENTE D'INVALIDITÉ | 69 al. 1 let. a LAI, 58 al. 3 LPGA